Magnetic properties of graphene quantum dots - Espinosa-Ortega, Tania (2014)
Using the tight-binding approximation we calculated the diamagnetic susceptibility of graphene quantum dots (GQDs) of different geometrical shapes and characteristic sizes of 2–10 nm, when the magnetic properties are governed by the electron edge states. Two types of edge states can be discerned: the zero-energy states (ZESs), located exactly at the zero-energy Dirac point, and the dispersed edge states (DESs), with the energy close but not exactly equal to zero. DESs are responsible for a temperature-independent diamagnetic response, while ZESs provide a temperature-dependent spin paramagnetism. Hexagonal, circular, and randomly shaped GQDs contain mainly DESs, and, as a result, they are diamagnetic. The edge states of the triangular GQDs are of ZES type. These dots reveal the crossover between spin paramagnetism, dominating for small dots and at low temperatures, and orbital diamagnetism, dominating for large dots and at high temperatures.